The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2105/ajph.2010.199455
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Ethnic Differences in Disease Burden and Disparities in Physical Function in Older Adults

Abstract: Objectives. We investigated whether a greater burden of disease among poorer individuals and ethnic minorities accounted for socioeconomic and racial disparities in self-reported physical functioning among older adults. Methods. We used data from adults aged 60 years or older (n = 5556) in the Third National Health and Nutrition Examination Survey, 1988–1994 to test associations between education level, poverty index, and race/ethnicity and limitations in 11 functions. We adjusted for demographic features and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 41 publications
7
55
0
Order By: Relevance
“…Racial differences associated with higher morbity 19,46,47 , obesity 9,15,22,29 and disability 16,28 are largely explained by unfavorable socioeconomic conditions, with lead to an accumulation of unhealthy behaviors and lifestyle, due to lower access to information, quality education and health services. According to Chor 20 , race, socioeconomic status and gender are crucial variables Table 4 Effect of race on body fat among diabetic elderly individuals according to gender, adjusted by schooling and family income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial differences associated with higher morbity 19,46,47 , obesity 9,15,22,29 and disability 16,28 are largely explained by unfavorable socioeconomic conditions, with lead to an accumulation of unhealthy behaviors and lifestyle, due to lower access to information, quality education and health services. According to Chor 20 , race, socioeconomic status and gender are crucial variables Table 4 Effect of race on body fat among diabetic elderly individuals according to gender, adjusted by schooling and family income.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic disparities in obesity, as with other health conditions, are well-established in the literature 12,13,14,15,16 . Race and ethnicity, demographic characteristics which are also widely correlated with socioeconomic status 17,18,19,20 , are associated with obesity, evaluated by anthropometric indicators of general (BMI) 7,9,21,22,23 and central fat (waist circumference -WC and waist-hip ratio -WHR) 9,24,25 .…”
Section: Introductionmentioning
confidence: 98%
“…Smoking behaviors is most worrisome for the one fifth of older single fathers who reported that their grandchildren/ children have asthma. Lifestyle choices about smoking and other health behaviors are especially important to study with male-headed families from low-SES backgrounds because research has suggested that adverse health outcomes are more prevalent in these families (Harvey & Ogden, 2014;Louie & Ward, 2011;Sheffer et al, 2012). Improving access to smoking cessation programs and targeted messaging that emphasize the hazards of passive smoke to children is warranted (Pisinger, Hammer-Helmich, Andreasen, Jorgensen, & Glumer, 2012).…”
Section: Physical Health and Health Behaviorsmentioning
confidence: 99%
“…One pathway is by enhancing an individual’s ability to prevent and control chronic diseases. However, socioeconomic disparities in physical capacity are consistently found after accounting for health behaviors and presence of chronic diseases, suggesting additional pathways (Coppin et al, 2006; Lantz et al, 2001; Louie & Ward, 2011; Thorpe et al, 2011; Zaninotto et al, 2013). …”
Section: Introductionmentioning
confidence: 99%